A Message from the Desert - Luis Ibarra; Teresa Rosano (Oz, 2003)
We were shot in the middle of the desert by a hippie chick in a van. Actually it was a photo-shoot for Architecture Magazine last year. We were one of nine architecture design firms chosen by the magazine and told to meet in the parking lot of a Quick Mart in Apache Junction, Arizona, about thirty miles east of Phoenix.